Yes, but, No, but: A contrarian response to Cross (2014). (November 2014) - Ansdell, Gary
This text responds to Ian Cross' article 'Music as Communication' from a music therapist's perspective. Its response is both appreciative – acknowledging the emerging consilience between aspects of music psychology and music therapy at a disciplinary level – but also contrarian, challenging whether a materialist-reductionist epistemology/methodology can form a sufficient framework for understanding how music helps within music therapy and other music and wellbeing practices. The article suggests that a broader conceptual frame of 'musical relationship' is substituted for the narrower one of 'musical communication, ' and a more expansionist perspective is taken to tracing and exploring the health-promoting ecology of musical people, musical things, and musical situations.